Association between employment status and risk of all-cause and cause-specific mortality: a population-based prospective cohort study. Issue 5 (21st February 2020) - Nie, Jing; Wang, Jianglin; Aune, Dagfinn; Huang, Wentao; Xiao, Dong; Wang, Yafeng; Chen, Xiong
Abstract : Background: Unemployment has been reported to be associated with an increased risk of mortality. While most available studies focused on the effects of temporary unemployment on mortality, it remains unclear whether similar trends can be found in subjects who were never employed or are retirement. Therefore, this study examined the associations between temporary unemployment, never employed and retirement, integrating the risk of all-cause and cause-specific mortality in US adults. Methods: Data from the National Health Interview Survey from 2001 to 2013 Linked Mortality files through 31 December 2015 were used. A total of 282 364 participants aged 18 to 65 years were included. Their employment status was categorised into four groups: employed, never employed, temporary unemployed and retired. Results: During the mean follow-up time of 8.2 years, 12 645 subjects died from a variety of causes. Compared with employed participants, temporary unemployed, never employed or retired participants faced an increased risk of mortality for all-cause (temporary unemployed HR 1.76, 95% CI 1.67 to 1.86; never employed HR 1.63, 95% CI 1.47 to 1.81; retired HR 1.27, 95% CI 1.17 to 1.37). Cause-specific mortality analysis showed that compared with employed participants, temporary unemployed or never employed participants faced a significantly increased risk of mortality from cancer, cardiovascular disease, chronic lower respiratory disease, diabetes and kidney disease. Conclusion: This study showed that retired, temporary unemployed and never employed participants aged 18 to 65 years were strongly associated with higher mortality, indicating that both temporary and long-term unemployment are associated with a higher risk of mortality and adversely affect longevity.